Cell penetrating thiazole peptides inhibit c-MYC expression via site-specific targeting of c-MYC G-quadruplex. Issue 11 (14th May 2018) - Dutta, Debasish; Debnath, Manish; Müller, Diana; Paul, Rakesh; Das, Tania; Bessi, Irene; Schwalbe, Harald; Dash, Jyotirmayee
Abstract: The structural differences among different G-quadruplexes provide an opportunity for site-specific targeting of a particular G-quadruplex structure. However, majority of G-quadruplex ligands described thus far show little selectivity among different G-quadruplexes. In this work, we delineate the design and synthesis of a crescent-shaped thiazole peptide that preferentially stabilizes c-MYC quadruplex over other promoter G-quadruplexes and inhibits c-MYC oncogene expression. Biophysical analysis such as Förster resonance energy transfer (FRET) melting and fluorescence spectroscopy show that the thiazole peptide TH3 can selectively interact with the c-MYC G-quadruplex over other investigated G-quadruplexes and duplex DNA. NMR spectroscopy reveals that peptide TH3 binds to the terminal G-quartets and capping regions present in the 5′- and 3′-ends of c-MYC G-quadruplex with a 2:1 stoichiometry; whereas structurally related distamycin A is reported to interact with quadruplex structures via groove binding and end stacking modes with 4:1 stoichiometry. Importantly, qRT-PCR, western blot and dual luciferase reporter assay show that TH3 downregulates c-MYC expression by stabilizing the c-MYC G-quadruplex in cancer cells. Moreover, TH3 localizes within the nucleus of cancer cells and exhibits antiproliferative activities by inducing S phase cell cycle arrest and apoptosis.